THE USE OF HAND PUPPETS TO IMPROVE SPEAKING SKILLS IN EARLY CHILDHOOD AT RA DARUNNAJAH - Hadiniyah, Nur; Wahyuni, Akhtim (Antis Publisher, 2025)
Objective: This research aims to improve speaking skills in early childhood at RA Darunnajah through the use of hand puppets as an interactive learning media. Methods: A classroom action research design with two cycles was used, involving direct observation, interviews, and documentation. The study focused on measuring the effectiveness of hand puppets in enhancing speaking skills. Results: The use of hand puppet media significantly increased children’s active participation in speaking, expanded their vocabulary, and boosted their self-confidence. Storytelling activities with hand puppets created a dynamic and engaging learning environment that supported language development. Novelty: This study highlights the impact of creative media, such as hand puppets, on improving early childhood speaking skills, especially for children who are shy or lack confidence in speaking.